The Mechanisms of Immune System Regulation by Probiotics in Immune-Related Diseases - Parvin Bastani,; Aziz Homayouni,; Leila Norouzi-Panahi,; Arash Tondhoush,; Sharareh Norouzi,; ElnazVaghef Mehrabany ,; Zahra Kasaie, (Journal of Pharmacy and Nutrition Sciences, 2016)
Probiotics are live microorganisms which when administered in adequate amounts, may confer a health benefit on the host. Stimulation and regulation of immune system is among well documented benefits claimed for probiotics. Both innate and adaptive immune system can be regulated by these microorganisms. Effects of probiotics on immune system are significantly dependent on the strain, dosage and the investigated condition. In this article the mechanisms through which probiotics may regulate immune system were reviewed. These mechanisms are consist of blockage of adhesion sites for pathogenic bacteria, competition for nutrients, production of inhibitory compounds, degradation of the toxin receptors in the mucosa membrane, activation of phagocytic and natural killer cells as well as regulation of cellular and humoral immunity. Also the immune-related diseases including immune deficiency (Acquired immunodeficiency syndrome) and hypersensitivity (allergy, inflammatory bowel disease, diabetes mellitus type 1 and rheumatoid arthritis) were discussed